1987
DOI: 10.1007/bf00288852
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variation in rye, Secale cereale L.

Abstract: Eleven samples of eight European commercial varieties of winter rye were examined at eight polymorphic enzyme loci. Genotype frequencies fitted Hardy-Weinberg expectations at all loci in all samples studied. Of the total genetic diversity recorded at the 8 loci, only 7% was expressed between varieties. Allele frequency differences between varieties were, however, sufficient to allow a characterization of each variety by a specific set of allele frequencies. Using subsets of the original data, it could be demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
3
16
1
Order By: Relevance
“…Though there have been some concerns about the reliability of RAPD markers and their ability to detect variation at high frequency (Riedy et al ., 1992 ;Ellsworth et al ., 1993), the optimization of experimental protocols for each particular situation have allowed RAPD analyses to provide information on taxonomic and phylogenetic relationships in a large number of plant genera and species, 'Carokurz' 'Kustro' 'Kungs II' 'Carogold' 'Halo' Fig. 1 . Relationships between some of the rye varieties studied based on Adam et al . (1987) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there have been some concerns about the reliability of RAPD markers and their ability to detect variation at high frequency (Riedy et al ., 1992 ;Ellsworth et al ., 1993), the optimization of experimental protocols for each particular situation have allowed RAPD analyses to provide information on taxonomic and phylogenetic relationships in a large number of plant genera and species, 'Carokurz' 'Kustro' 'Kungs II' 'Carogold' 'Halo' Fig. 1 . Relationships between some of the rye varieties studied based on Adam et al . (1987) .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to compare the groups of cultivars, based on genetic similarity, generated by each type of marker. Since previous estimates have been made of the genetic distances between these cultivars, based on isozymes analysis (Adam et al ., 1987), the comparison of techniques could be further extended .…”
Section: Introductionmentioning
confidence: 99%
“…nigra and other poplars . This method of clonal identification is reliable, precise, simple, fast, objective and inexpensive and can be applied to living (Bassiri & Adams, 1978) or based on the presence or absence of each allozyme (Oliver & Martinez-Zapater, 1985) or Nei's (Nei, 1972) genetic distances (Adam et al ., 1987 ;Glaszmann, 2 0 5 1987) . In recent studies, multivariate analysis of multilocus allozyme data has been found to show greater sensitivity and statistical significance (Yeh et al ., 1985(Yeh et al ., , 1986) as this has been observed to account for interactions among isozyme loci that are not observable using averaging techniques such as Nei's genetic distance .…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of differences in the allele frequency between populations was tested by means of a likelihoodratio test G 2 (Adam, 1987). Genetic identity (I) and genetic distance (D) between local populations were estimated after Nei (1972).…”
Section: Methodsmentioning
confidence: 99%